MANAGEMENT OF ERECTILE DYSFUNCTION IN CARDIOVASCULAR PATIENTS WITH COMORBIDITIES: REVIEW OF THE TRIALS ON CONTINUING THERAPY WITH PHOSPHODIESTERASE-5 MEDICATIONS - G. G. Sharvadze; R. R. Dalari; B. U. Mardanov; M. N. Mamedov (Кардиоваскулярная терапия и профилактика)
The review is focused on the issues of erectile dysfunction (ED) management by long term courses of continuous intake of the phosphodiesteraze-5 type (PDE5) inhibitors. ED is an actual problem of modern healthcare, prevalent and influencing negatively life quality and interpersonal relations. At early stages the management of ED by the PDE5 inhibitor drugs was regarded as symptomatic. However recently there are more and more publications that confirm continuous long term intake of PDE5 inhibitors. This can be explained by the mechanism of this drugs class action that includes the causation of the disorder, particularly, endothelial dysfunction. It is well konwn that in erectile dysfunction there is malfunction of nitric oxide synthesis by endothelium, and long term usage of PDE5 facilitates the increase of biochemical reactions that can be started by nitric oxide. Based on the review data, a proposition made that PDE5 inhibitors are not harmful for cardiovascular system, but may present with positive effects on cardiovascular system in general. The trials towards this direction continue. There is also a suggestion that intake of PDE5 inhibitors helps to restore normal endothelial function that may lead to better condition of cardiovascular system and decrease complications rate.